High-density risers as reactor system for benzene synthesis by non-oxidative dehydroaromatization of methane - fluid-dynamic investigations - Hensler, Timo; Zhang, Yingxue; Mleczko, Leslaw; Assmann, Jens; Bellinghausen, Rainer; Schwieger, Wilhelm; Wirth, Karl-Ernst (11th International Conference on Fluidized Bed Technology, CFB 2014, 2014)
As a precursor for synthesis of dyes, polymers, fuel additives and various solvents benzene has become an indispensable base chemical in a large field of industrial processes. To date the industrial benzene demand is covered in large part by benzene which is extracted from crude oil. However, scarcity of oil resources accompanied by increasing prices for oil derived chemicals necessitates the development of alternative processes to satisfy the market's benzene demand. The presented work deals with the development of a reactor model for benzene synthesis by non-oxidative dehydroaromatization of methane. Based on model calculations a riser reactor operated at high solids concentrations has been found to allow for most efficient operation. Together with the model experimental data are presented in order to evaluate the fluid-dynamic feasibility of the suggested flow condition within a pilot plant scale circulating fluidized bed. Experimental data show that stable operation can be achieved at cross-section averaged solids concentrations up to 30 vol.%.